Dampak Media Youtube terhadap Hasil Belajar Siswa pada Pembelajaran Instalasi Penerangan Listrik - Ilfani Hamzah; Usmeldi Usmeldi (Jurnal Pendidikan Teknik Elektro, 2022)
This study aims to determine the impact of the use of youtube in learning. The learning process at this time has been influenced by information and communication technology. To improve student learning outcomes of SMK Negeri 1 Padang, a more interesting and interactive learning media is needed. This research was conducted using the type of experimental research which is categorized into a quasi-experimental research type with the pretest-posttest group design method, namely one experimental class that will be applied to learning using YouTube Electrical Installation content and one control class that does not use YouTube in its learning. The subjects of this study were students of class XI TITL SMK Negeri 1 Padang in the academic year 2022/2023a. To measure the impact, a pretest was given before the students applied learning using YouTube. Then the Posttest was given after the learning process of Electrical Power Installation. Posttest results were analyzed using a series of tests such as t-test and effect size. The results of the test show that the scores of students who applied learning using YouTube's Electrical Installation content were better than students who did not use YouTube. Student learning outcomes after using youtube increased. So that the use of YouTube media for Electrical Installation content has a positive impact in improving student learning outcomes.